Boolean network model for simulation of cellular signalling & gene expression - Chen, Haoting (2015)
Signalling pathways are the foundations to comprehend cell functions and forecast cell behaviours. Cells can transfer external stimuli to prompt various biochemical reactions, which include transcription factor activities throughout signal transduction, leading to different gene expressions. The main objective of this project is to understand the correlation between the external stimuli and the consecutive cellular responds along with the following effects on the downstream genes. This project is implemented on the base of a Cytoscape plugin called SimBoolNet, which uses the Boolean Network models to simulate the dynamic process of signal transductions, and combine it with the Network Component Analysis (NCA), which can establish a gene regulatory network (GRN) from the temporary gene expression data and connectivity relationships between transcription factors and their respective targeted genes.